Impact of different embryo loading techniques on pregnancy rates in in vitro fertlizaton/embryo transfer cycles - Iman Halvaei; Mohammad Ali Khalili; Mohammad H Razi; Azam Agha-Rahimi; Stefania A Nottola (Wolters Kluwer Medknow Publications, 2013)
Background: Embryo transfer (ET) technique is one of the important factors of in vitro fertlization success. Among the different steps in ET technique, less attention has been given to embryo loading (EL). The aim was to compare the impact of two different techniques of EL on pregnancy rate in IVF/ET cycles. Materials and Methods: In this retrospective study, 144 and 170 patients were placed in groups A and B, respectively. In Group A, the embryos were drawn directly into the ET catheter from culture microdrop under the oil. In Group B, the embryos were transferred from culture microdrop into G2 medium in center-well dish. Then, the embryos were drawn into the catheter and finally transferred into the uterus. Both groups were adjusted for other parameters based on the EL technique. The main outcome measure was pregnancy rate. Results: There were insignificant differences for etiology of infertility, source of sperm, type of stimulation protocol, percent of IVF or intracytoplasmic sperm injection type of ET catheter, cycles with good quality embryos and transferred embryos between two groups. The rate of both chemical and clinical pregnancy was higher in Group B compared to A, but the difference was insignificant (P = 0.09 and P = 0.1, respectively). Conclusion: It seems that there is no difference in the outcome by loading the embryo from microdrop or center-well dish.